DATUK PROFESSOR DR. ASMA ISMAIL, USM’S NEW VICE-CHANCELLOR - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 30 September 2016 The DirectorGeneral of Higher Education, Ministry of Higher Education Malaysia, Datuk Professor Dr. Asma Ismail has been appointed as the new ViceChancellor of Universiti Sains Malaysia (USM) effective from Tuesday, 4 October 2016 for three years, taking over from Professor Dato' Dr. Omar Osman, who had been in office since 27 September 2011.